Mixed Nothofagus forest management: a crucial link between regeneration, site and microsite conditions - Sola, Georgina Giselle (2019)
Canopy openings due to harvesting practices constitute a disturbance that changes the environmental conditions of microsites. Its impact on the relative performance of the regeneration of different tree species could also be affected by site conditions and forest structure.The objective of this study was to determine how regeneration establishment of Nothofagus mixed forests is influenced by shelterwood silvicultural system. We focused on Lanín National Reserve (Neuquén, Argentina) where this silvicultural system has been applied since the late 1980s. The microsite scale analysis (one managed forest) showed that canopy cover was a key factor conditioning Nothofagus regeneration establishment, with older and larger individuals growing in less exposed microsites. Low understory dominance and leaf litter thickness were also associated with microsites with regeneration, while successful establishment (saplings taller than 2 m) showed positive correlation with soil moisture. Variations of these patterns were observed among species reflecting their specific ecophysiological requirements. On a stand scale (two managed forests along Lacar watershed) regeneration of N. dombeyi and N. alpina showed significant correlation with site and specific basal area, while N. obliqua was correlated with total basal area. Regeneration taller than 2 m was mainly correlated with site and altitude. At both, microsite and stand scale, the relative abundance of species changed between mature trees and regeneration. In particular, for N. alpina, an abundance decrease was observed on regeneration. Our results suggest that forest management systems should diversify silvicultural practices throughout the forest landscape, to provide at each site the micro-environmental conditions required by each species in order to maintain biodiversity and forest functions.